Frustration discomfort and growth mindsets of preservice teachers in mathematics - Udell, Ashley Lauren (Kansas State University, 2022)
Undergraduate students in an education program, or preservice teachers, are expected to practice and teach productive struggle in mathematics as they prepare for their career. Productive struggle in mathematics requires students to persevere in solving rigorous tasks, despite their frustration in doing so. Therefore, a student’s level of frustration discomfort and the degree to which they have a growth mindset may impact their ability to practice productive struggle. Is there a relationship between a student’s degree of growth mindset and their level of frustration discomfort? This study used a correlation research design to investigate a relationship, if any, between degrees of growth mindset and levels of frustration discomfort among preservice teachers.
Keywords: Frustration discomfort scale; Theories of intelligence scale; Growth mindset; Mathematics education; Preservice teachers; Productive struggle